From emigrant to rebel: José Canterac, an undesirable soldier in search of a lost identity - Tauzin-Castellanos, Isabelle (2019)
Son of French counterrevolutionary emigrants, Canterac came to be a model officer of the Royal army of Fernando VII. In 1821 he was part of the group of senior officers who forced the viceroy to renounce, in the first coup in the history of Peru; he signed the capitulations of Ayacucho, with whom Spain lost continental America. Canterac returned to France in 1825 and tried to approach Fernando VII. In this biography the reports and letters from various sources will be so many forgotten writings thanks to which the present research wants to take part in the construction of a renewed history of independence, beyond the limitations of national histories.